An Analysis of Factors Associated with Anxiety in Pregnant Women - Putri Nadillah Isti; Dwi Ernawati; Ririn Wahyu Hidayati (Sarana Ilmu Indonesia (Salnesia), 2026)
Anxiety during pregnancy has the potential to affect the psychological and physical well-being of both the mother and the fetus. If not properly managed, this anxiety can persist into the postpartum period and increase the risk of postpartum depression, labor complications, preterm birth, and low birth weight (LBW) infants, as well as potentially hinder fetal brain development. This study aimed to identify factors associated with anxiety among pregnant women at the Sleman Community Health Center in Yogyakarta. This study was a quantitative survey using a cross-sectional study design. The study subjects consisted of 105 individuals who met the inclusion criteria and were selected using purposive sampling. Data collection was conducted using the PASS (Perinatal Anxiety Screening Scale) questionnaire, and analysis was performed using Fisher’s Exact test. The results showed that 51 subjects (48.6%) experienced mild to moderate anxiety. In addition, this study found a significant association between the age of pregnant women and anxiety (p = 0.041). However, no significant association was found between the number of pregnancies (p = 0.063), gestational age (p = 0.275), educational level (p = 0.143), and economic status (p = 0.904) and maternal anxiety. The factor associated with anxiety in pregnant women is maternal age, whereas the number of pregnancies, gestational age, education, and economic status do not influence anxiety in pregnant women. The results of this study support the importance of support through health policies.